Islam in Indonesia During the Dutch Colonial Rule - Putri Hafidzah; Risma Euis Patonah; M. Zaki Rizanata (Penerbit Hellow Pustaka, 2025)
Islam in Indonesia during the Dutch colonial period. The research utilizes a literature review method, analyzing various historical sources and relevant literature to uncover the dynamics of Islam in the colonial context. was not just a religion, but also a political and ideological force that influenced Indonesian history. Since its initial arrival, Islam has been a significant political force in Indonesia. Islamic sultanates played a crucial role in expanding the influence of the religion, confronting Western colonialism, and establishing a strong political identity in the archipelago. Islam in confronting colonialism. Resistance to colonialism and the VOC's trade monopoly demonstrates the central role of Islam in the history of Indonesia's struggle. The Aceh War (1873 - 1912), led by scholars and sultans, is a prime example of how pesantren and scholars played a role in resisting colonialism. The article further highlights the vital role of pesantren as centers of religious and cultural instruction, as well as places for nurturing national leaders and anti-colonial movements. Pesantren taught students to fight injustice and oppression, fostering a sense of nationalism among Muslims. Through pesantren, Islam not only taught spiritual values but also moral and social values that encouraged the struggle for independence. In the early 20th century, scholars began to adopt a new, more organized approach through the formation of organizations such as Muhammadiyah and Nahdlatul Ulama. These organizations became platforms for Indonesian Muslims to engage in structured action to fight for independence and national progress. Overall, the article demonstrates that Islam has been an influential force in Indonesian history, both in confronting colonialism and in building a national identity. The struggle of Muslims, manifested in various forms of resistance and movements, has made a significant contribution to shaping the history and future of the Indonesian nation. This article underscores that Islam plays a role not only in spiritual life but also in social, economic, and political life, becoming a force driving change and progress in Indonesia.